2017
DOI: 10.5847/wjem.j.1920-8642.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation knowledge and attitude among general dentists in Kuwait

Abstract: BACKGROUND:Dentists as health care providers should maintain a competence in resuscitation. This cannot be overemphasized by the fact that the population in our country is living longer with an increasing proportion of medically compromised persons in the general population. This preliminary study aimed to assess the knowledge and attitude of general dentists towards cardiopulmonary resuscitation (CPR). METHODS:A cross-sectional study was carried out among 250 licensed general dental practitioners working in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
3
12
2
1
Order By: Relevance
“…In our study, all HCP performed poorly on the written and practical assessment on the initial approach, with less than one third of HCP correctly identifying the importance of scene safety, checking for responsiveness and calling for help. These observations are similar to what has been reported in other low-and-middle income countries [ 27 , 28 ], and contrary to findings of similar studies in high-income countries [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, all HCP performed poorly on the written and practical assessment on the initial approach, with less than one third of HCP correctly identifying the importance of scene safety, checking for responsiveness and calling for help. These observations are similar to what has been reported in other low-and-middle income countries [ 27 , 28 ], and contrary to findings of similar studies in high-income countries [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…In New Zealand, more than half of the dentists surveyed were not satisfied with the medical emergency training given during their undergraduate education and 14.1% considered themselves not adequately prepared for an emergency in practice. In Kuwait, the majority of general dentists have inadequate knowledge of CPR and only 57.2% feel competent in performing CPR; however, 99% agree that dentists should be able to apply CPR. A study conducted in Western Saudi Arabia revealed that only 11% of dentists assessed vital signs during each visit, and the mean level of self‐assessed preparedness for medical emergencies was 55.2 ± 20 on a scale of 0–100.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of publications on medical emergencies in dental offices in different countries have appeared 5,6,9,10,[21][22][23][24][25][26] . Much research on the attitudes and skills of dentists has focussed on CPR in dental office settings and the dentists' preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, a survey showed out of 533 people, only 3.6% can perform bystander CPR, and 15.6% answered the right compression-ventilation rate [ 28 ]. In a very recent study targeting the general dentists in Kuwait, 64% showed low knowledge, while only 36% have high knowledge about CPR [ 29 ]. In Saudi Arabia, few studies about CPR knowledge were conducted in a study on 753 subjects in Al-Khobar city in which 80.8% of the females and 86.5% of the males were totally unaware of CPR; however, 88.7% of all participants were willing to attend CPR courses in the future [ 30 ].…”
Section: Introductionmentioning
confidence: 99%